Transoral laryngeal microsurgery for early-stage laryngeal basaloid squamous cell carcinoma. Issue 12 (30th December 2021) - Verro, Barbara; Saraniti, Carmelo
Abstract : A 71-year-old man presented to our otolaryngology clinic with dysphagia and dyspnoea. He had a history of smoking for 40 years. Laryngoscopy showed an exophytic, round mass on the left aryepiglottic fold that was entirely excised by transoral laser CO2 microsurgery. Histological assessment revealed a pT1 basaloid squamous cell carcinoma (BSCC) with free-margin resection. He underwent close follow-up and after 3-year follow-up, the patient was free from disease. Laryngeal BSCC is a rare cancer with poor prognosis due to its late diagnosis and early neck node metastases. We report a rare case of early tumour treated by endoscopic surgery without complications or recurrence of disease. However, knowing this type of cancer and making a correct differential diagnosis are important to guarantee the best therapy and prognosis.